Stored Product Pests - P.G. Koehler; W.H. Kern, Jr.; J.L. Castner (EDIS)
This document provides an overview of common stored product pests, including beetles and moths, that infest food products. It details the characteristics, life cycles, and behaviors of pests such as the rice weevil, lesser grain borer, flour beetles, sawtoothed grain beetle, cigarette beetle, drugstore beetle, and various weevils and moths. The article emphasizes the importance of identifying these pests to manage and prevent infestations effectively. It also includes visual aids to help with identification and offers insights into the damage these pests can cause to stored food products. Date first printed: November 1992.